p-9=-5(p-3)

Simple and best practice solution for p-9=-5(p-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for p-9=-5(p-3) equation:



p-9=-5(p-3)
We move all terms to the left:
p-9-(-5(p-3))=0
We calculate terms in parentheses: -(-5(p-3)), so:
-5(p-3)
We multiply parentheses
-5p+15
Back to the equation:
-(-5p+15)
We get rid of parentheses
p+5p-15-9=0
We add all the numbers together, and all the variables
6p-24=0
We move all terms containing p to the left, all other terms to the right
6p=24
p=24/6
p=4

See similar equations:

| .15-3x=-6 | | 7(x+2)-1=3x+4(3+x) | | -8x-7=-3x-17 | | 6x+5-9x=-40 | | 7x=7(7)=0 | | (2x²-3x+1)=+(4x-7) | | 0.66666667n-5=-2 | | 14=2(r-9) | | –10b−3+3b=4−6b | | 10m-19=3m+2 | | 4u+5=37 | | -7(4x+7)=3+4(-4-6) | | 15(x+14)=60 | | T(12)=5n-6 | | -8x3=-6x11 | | -11=k+(+5) | | 9x+54=99 | | -8x+10+4x=38 | | 36=t-3t+26 | | 2x+5+2x+5=58 | | 3(x-4)-(x-2)=0 | | 13-4x=-12 | | 0.66n-5=-2 | | 11x+16=-49 | | 8/n=2/4 | | (x+2)x2-3=1 | | -3r-2=6-4r | | 0.67n-5=-2 | | 16c-13c+3c+c+1=8 | | 2x+20-x=-60 | | 5=1/2(3x+8) | | 9x+5=1(x+3) |

Equations solver categories